Management of bakanae disease using fungicides and their effect on disease symptomatology - BASHYAL, BISHNU MAYA; GUPTA, ASHISH KUMAR; PARMAR, POOJA; YADAV, JAGDISH; CHOUDHARY, RAVISH; KUMAR, RAVINDRA; SINGH, DHIRAJ; AGGARWAL, RASHMI (The Indian Journal of Agricultural Sciences, 2022)
Bakanae disease is an emerging problem of Basmati rice (Oryza sativa L.) in India and most of the basmati rice varieties are susceptible to this disease. Present study was carried out to evaluate and identify effective fungicide against bakanae disease of rice for which 12 fungicides (single and in combination) were evaluated against the bakanae disease as seedling treatments during the rainy (kharif) season of the year 2019 and 2020. Minimum disease incidence was observed with the fungicides Carbendazim 50% wp (19.47%), and Tebuconazole 50% + Trifloxystrobin 25% w/w 75 wg (25.71%) during the years of evaluation with maximum yield. Area under disease progress curve was minimum (621.58) with the treatment of Tebuconazole 50% + Trifloxystrobin 25% w/w 75 wg followed by Carbendazim 50% wp (671.30). Differences in bakanae disease symptoms were observed in different treatments. Among treatments, elongated tillers as major symptoms were observed in Mancozeb 75% wp, Zineb 68% + Hexaconazole 4% and Azoxystrobin 23% sc treated plants. Whereas, tiller elongation with rotting was prominent in Kitazin 48% ec treated and inoculated control plants. In case of Carbendazim 50% wp, Tebuconazole 8% + Captan 32% sc treatments, detachment of tillers was prominent. Therefore, seedling treatment with fungicides was observed to be effective in reducing bakanae disease incidence with low AUDPC and high yield compared to inoculated control.